Skema Pembiayaan Partai Politik untuk Meminimalisir Korupsi Politisi - Hadi Kusuma, Achmad Surya (CV. Era Digital Nusantara, 2023)
Party financing is one of the most important issues in Indonesia’s political system. The source of funding as well as what the funds are used for are big questions that need to be answered. This article uses a systematic literature review method to answer the question of how to minimize politician corruption through political party financing schemes. The problem relates to how politicians and political parties get their funds and what the funds are used for. This article also provides a comparison with four OECD countries that will provide an overview of what a party funding scheme should look like.